Three new species of the genus Viettherchnus Kirejtshuk, 1985 (Coleoptera: Nitidulidae: Nitidulinae: Cyllodini) - Jelínek, Josef; Hájek, Jiří (Zootaxa, 2024)
Three new species of the genus Viettherchnus Kirejtshuk, 1985 are described and illustrated: Viettherchnus apriculus sp. nov. (Malaysia), V. helferi sp. nov. (Indonesia: Kalimantan, Malaysia, Myanmar) and V. orszuliki sp. nov. (Nepal); the latter represents the first species of the genus known from the Himalayas. An identification key to all Viettherchnus species is provided.